MICROSERVICES: a case study pointing out its potential - Domingos, Leonardo Luis; Farina, Renata Mirella (Revista Interface Tecnológica, 2020)
This article aims to point out potentialities and advantages of using microservice architecture compared to monolithic architecture. The methodology used refers to a case study with a qualitative approach. The case study presents the migration of an e-commerce system, initially built with monolithic architecture, to a microservice architecture. According to the results, it is concluded that an application in microservices architecture ends up reflecting on several benefits, such as ease of maintenance, scalability of services, low coupling and independence. In this way a problem does not affect the rest application, thus demonstrating the advantages of choosing microservices.